Kebijakan Kepala Sekolah dalam Meningkatkan Pelayanan Administrasi di Sekolah Menengah Atas Negeri 4 Merangin Provinsi Jambi - Rifa Hatul Baiyanah; Riftiyanti Syafitri; Hamdi Zas Pendi (Jurnal Manajemen dan Pendidikan Agama Islam, 2024)
The principal's policy in improving administrative services aims to create an efficient and effective school environment. The principal's policy in improving administrative services is a systematic effort to improve and increase the efficiency and effectiveness of administrative services in the school environment. This involves developing procedures, empowering staff, investing in technology, and implementing good management principles. This research uses a qualitative descriptive approach, collecting data through observation, interviews and documentation. The collected data was analyzed through a process of data reduction, presentation and drawing conclusions. The research findings show that the principal's policy in improving services is to carry out open communication both formally and informally. And another thing that supports improving administrative services is good human resources. The first obstacle is limited education funds, namely that it is difficult to provide facilities in the administration department, such as broken computers at school, and the second obstacle is poor discipline of teachers and staff, which is the cause of services at SMA Negeri 4 Merangin decreasing or not being good. And the solution to overcoming obstacles is maximizing funds, namely the principal makes a report first to the department or center, if there is not yet a principal, calls a meeting between the deputy and the treasurer to discuss together, and the second solution regarding discipline is that the principal tries to be an example or role model. first of all towards teachers, staff and students at the school, apart from that the principal will be strict with school members who violate it by calling them immediately to the office and asking for information after which they will be given sanctions.